Peran Guru PAI dalam Pelaksaan Program Tahfidz di SMP Negeri 1 IV Koto - Resa Pini Nosa; Hidra Ariza; Nurfatmi Nurfatmi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This article discusses the role of PAI teachers in implementing the Tahfidz Program in Junior High Schools (SMP). Not only does it require the participation of children and educators to help improve memorization of the Al-Quran/tahfidz, but the help of parents is also needed. This article also explains the involvement of parents in facilitating children's learning goals, where parents can guide their children to always learn to read the Al-Quran and memorize the Al-Quran after every Maghrib prayer so that children get used to it until they grow up. This research is motivated by the importance of increasing memorization of the Koran from an early age. The aim is to introduce children to the benefits of reading the Al-Quran every day and so that children can become great Hafidz of the Al-Quran. The type of research used by the author is qualitative research with a descriptive approach, to obtain data from the problems studied, the data collection techniques used by the author include observation, interviews and other documentation. The Tahfidz program is one of the efforts that can be made to help children read and memorize the Al-Quran every day and give birth to many pious children who will definitely give birth to Al-Quran hafidz children in the future. Currently, there are still many children who do not read the Al-Quran fluently and some even do not know the Hijaiyah letters, making it difficult for them to read and memorize the Al-Quran.